Globalisasi dan Tantangan Identitas Keislaman: Analisis Perspektif Pendidikan Islam - Syafri Royyan Abdillah; Faturrahman Muhtar; Ismail Thoib; Era Mutiara Pratiwi; Gazi Saloom (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Islamic education faces significant challenges in the era of globalization, marked by technological advances, the rapid flow of information, and shifts in cultural values. In this context, Islamic education is required to maintain its Islamic values ​​while adapting to the times. This article aims to examine the challenges faced by Islamic education in addressing the challenges of Islamic identity among students in the era of globalization. This study uses a descriptive qualitative approach, where data is collected through library research methods, including relevant articles, journals, and books. This study examines literature related to the impact of globalization on Muslim identity, the challenges of Islamic education in shaping Muslim character in the era of globalization, and the identity crisis experienced by young people, including students, in Islamic education today. The results show that globalization, while carrying the risk of moral degradation and an identity crisis, also presents significant opportunities for the advancement of Islamic education through learning innovation and easy access to knowledge. Therefore, Islamic education needs to develop strategies based on the values ​​of the Qur'an and the Sunnah in a holistic and applicable manner. These strategies include character building and the integration of science, technology, and religion. With the right strategy, Islamic education is expected to be able to form a generation that is intellectually superior, spiritually strong, and morally resilient in facing global challenges